Gestión de ventas de la Empresa Femar de la ciudad de guayaquil en el periodo 2023. - Martínez Tapia, Karla Azucena (2025)
This study analyzes the sales management of FEMAR company in Guayaquil during 2023. Identified issues include a lack of standardized processes, low sales team motivation, and poor coordination with the marketing department. Through interviews and surveys, the study found that internal factors such as insufficient training and ineffective tools affect commercial performance, while external factors like economic conditions and competition also impact sales. The study recommends implementing a structured sales plan, improving staff training, and considering external factors when designing commercial strategies to enhance the company’s performance.